Specific interactions between lectins and red blood cells of chornobyl cleanup workers as indicator of some late radiation effects - Karpova, I.S. (Experimental Oncology, 2016)
Aim: Growing interest in lectins is based on their diagnostic and pharmacological potential, especially the ability to inhibit proliferation and initiate apoptosis of cancer cells. In our research microplate lectinoassay able to detect carbohydrate containing structures (receptors) on erythrocyte surface have been proposed for Chornobyl cleanup workers (1986) monitoring. It was expected to reveal specific abnormalities associated with pathological condition arising as a result of late radiation effects. Materials and Methods: Red blood cell (RBC) specimens were taken from 171 persons distributed into the six cohorts: nonexposed donors (1); chronically exposed to the doses below (2) and over 50 cGy (3); exposed to acute radiation without (4) and with manifestation of acute radiation syndrome (5 and 6). Lectins from 24 species of medicinal plants were purified by ethanol fractionation and electrofocusing. Intensity of lectin-receptor interactions was determined in reaction of hemagglutination. Method of flow cytofluorometry was used to study B-cell counts. Hormone levels in blood serum were determined by radioimmunoassay. Results: An elevated ability of RBC to interact with the panel of lectins was found in all cohorts of exposed persons versus nonexposed donors, moreover, changes in the intensity of lectin-receptor binding depended on the dose of irradiation. Diagnostic value of specific RBC reactions with some individual lectins has been elucidated. Elevated intensity of RBC reaction with Zea mays lectin was accompanied by a decrease in serum content of thyroid hormones T4 and T3, as well as reduction of B-cell counts. In the case of Rubus caesius lectin the more intensive reaction with RBC, the higher level of hormone cortisol was observed. Conclusions: Deviations from donor’s norm in intensity of lectin — RBC interactions in radiation exposed men are supposed to carry information about negative changes in their health status following Chornobyl catastrophe and show the diagnostic potential. The most sensitive reactions have been associated primarily with shifts in endocrine and immune systems. This article is a part of a Special Issue entitled “The Chornobyl Nuclear Accident: Thirty Years After”.